THE AGROECONOMIC VALUE OF RUBUS LOGANOBACCUS L.H. BAILEY CULTIVATED IN THE CONDITIONS OF THE REPUBLIC OF MOLDOVA - Alexandru MÎRZA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The introduced Rubus loganobaccus cultivars 'Lincoln Logan', 'Tayberry Buckingham', 'Tayberry Medana' were studied under the conditions of the Republic of Moldova. The experiments were conducted in the National Botanical Garden (Institute), Republic of Moldova. It has been found that the plant of studied cultivars produces 65 - 75 fruits per floricane, with an average weight of 4.37-6.20 g, their sugar concentration was 9.6 - 11.8 % and the vitamin C 21.1 – 26.2 mg/100 g. The antioxidant value of the leaves constitutes IC50 = 53-56 mg/ml. The leaf dry matter of the researched cultivars contained 15.2 - 18.7% crude protein, 81-13.6 % ash, 7.9-12.5 % cellulose, 12.7-13.9 % hemicellulose and can be used to feed animals or as organic fertilizer in the hybrid berry plantations. When pruning the floricanes after harvest, the wood biomass obtained contained 48.5 % cellulose, 25.4 % hemicellulose with energy value of 18.5 MJ/kg and theoretical ethanol potential 557 L/t, it can be used to produce renewable energy. In the Republic of Moldova, the studied Rubus loganobaccus cultivars have agroeconomic value as a food, medicinal plants, also as fodder and energy biomass.